2015
DOI: 10.1371/journal.pone.0136541
|View full text |Cite
|
Sign up to set email alerts
|

Pain in Parkinson´s Disease: A Cross-Sectional Study of Its Prevalence, Types, and Relationship to Depression and Quality of Life

Abstract: Pain is an important and distressing symptom in Parkinson’s disease (PD). Our aim was to determine the prevalence of pain, its various types and characteristics, as well as its impact on depression and quality of life (QoL) in patients with PD. How pain differs in early- and advanced-stage PD and male and female PD patients was of special interest. One hundred PD patients on dopaminergic medications had a neurological examination and participated in a structured interview on pain characteristics and completed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
86
2
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(104 citation statements)
references
References 38 publications
5
86
2
11
Order By: Relevance
“…4, 8, 9, 11 The corresponding figures for the present study were: musculoskeletal, 84.8%; dystonic, 33.2%; radicular, 46.1%; central neuropathic, 31.5%; and oro-facial pain, 20.8%. The origin of musculoskeletal pain in PD is complex and is a mixture of nociceptive and neuropathic elements complicated by local joint related pain as well as parkinsonian rigidity and postures such as dystonia.…”
Section: Discussionsupporting
confidence: 65%
“…4, 8, 9, 11 The corresponding figures for the present study were: musculoskeletal, 84.8%; dystonic, 33.2%; radicular, 46.1%; central neuropathic, 31.5%; and oro-facial pain, 20.8%. The origin of musculoskeletal pain in PD is complex and is a mixture of nociceptive and neuropathic elements complicated by local joint related pain as well as parkinsonian rigidity and postures such as dystonia.…”
Section: Discussionsupporting
confidence: 65%
“…9,10 On the other hand, using the King's Parkinson's Disease Pain Scale (KPPS), 11 the syndromic nature of pain has been formally subdivided into several patterns. Prior research has shown that the prevalence of pain is 68 to 81% in PD patients [12][13][14] and that it can be manifested in several modalities, such as musculoskeletal (41-89%), dystonic (15-17%), radicular-neuropathic (27-32%), and central pain (4-22%). 2,12,[14][15][16][17][18] Furthermore, 35% of PD patients are affected by two types of pain, 10% by three, and 2% by four.…”
Section: Introductionmentioning
confidence: 99%
“…While this contrasts with clinical surveys which have shown the frequency and intensity of pain to be greater in advanced-stage compared to early-stage PD [59], this research refers primarily to musculoskeletal pain. While disease progression would be expected to intensify this type of pain due to increasing muscle rigidity or postural abnormalities [13], our findings suggest that changes in sensitivity to noxious input may occur early on and be relatively independent of motor function degradation.…”
Section: Independence Of Motor Impairment and Painmentioning
confidence: 89%